Real-life use of left ventricular circulatory support with Impella in cardiogenic shock after acute myocardial infarction: 12 years AMC experience. Issue 4 (June 2019) - Ouweneel, Dagmar M; de Brabander, Justin; Karami, Mina; Sjauw, Krischan D; Engström, Annemarie E; Vis, M Marije; Wykrzykowska, Joanna J; Beijk, Marcel A; Koch, Karel T; Baan, Jan; de Winter, Robbert J; Piek, Jan J; et al.
Aims: Mortality in cardiogenic shock patients remains high. Short-term mechanical circulatory support with Impella can be used to support the circulation in these patients, but data from randomised controlled studies and 'real-world' data are sparse. The aim is to describe real-life data on outcomes and complications of our 12 years of clinical experience with Impella in patients with cardiogenic shock after acute myocardial infarction and to identify predictors of 6-month mortality. Methods: We describe a single-centre registry from October 2004 to December 2016 including all patients treated with Impella for cardiogenic shock after acute myocardial infarction. We report outcomes and complications and identify predictors of 6-month mortality. Results: Our overall clinical experience consists of 250 patients treated with Impella 2.5, Impella CP or Impella 5.0. A total of 172 patients received Impella therapy for cardiogenic shock, of which 112 patients had cardiogenic shock after acute myocardial infarction. The mean age was 60.1±10.6 years, mean arterial pressure was 67 (56–77) mmHg, lactate was 6.2 (3.6–9.7) mmol/L, 87.5% were mechanically ventilated and 59.6% had a cardiac arrest before Impella placement. Overall 30-day mortality was 56.2% and 6-month mortality was 60.7%. Complications consisted of device-related vascular complications (17.0%), non-device-related bleeding (12.5%), haemolysis (7.1%) and stroke (3.6%). In a multivariate analysis, pH before Impella placement is a predictor of 6-month mortality. Conclusions: Our registry shows that Impella treatment in cardiogenic shock after acute myocardial infarction is feasible, although mortality rates remain high and complications occur.